Fifty key thinkers on language and linguistics - Thomas, Margaret (Margaret Ann), 1952- (Routledge key guides., 2011)
What was the first language, and where did it come from? Do all languages have properties in common? What is the relationship of language to thought? "Fifty Key Thinkers on Language and Linguistics" explores how fifty of the most influential figures in the field have asked and have responded to classic questions about language. Each entry includes a discussion of the person's life, work and ideas as well as the historical context and an analysis of their lasting contributions. Fully cross-referenced and with useful guides to further reading, this is an ideal introduction to the thinkers who have had a significant impact on the subject of language and linguistics.